Gastric Outlet Obstruction as a Result of an Inguinal Hernia - Luke Wohlford; Richard Bounds (Clinical Practice and Cases in Emergency Medicine)
Case Presentation: We present a case of a 79-year-old male with gastric outlet obstruction resulting from a stomach herniation through a large left inguinal hernia. Discussion: Stomach-containing inguinal hernias are a rare cause of gastric outlet obstruction. Treatment options range from conservative to surgical management. Once identified with imaging, prompt treatment should be initiated to prevent incarceration, strangulation, and gastric necrosis.